What’s changed in European (Union) Studies? - Steven Kennedy (Journal of Contemporary European Research, 2015)
I have been asked to reflect on my experience of 35 years publishing university textbooks in relation to the evolution and development of European Union Studies (which term I shall use to include the study of the EU’s earlier incarnations in the European Community/Communities).